Pengembangan Metode Percepatan Penjadwalan Pada Keterlambatan Proyek EPC Di Fase Pelaksanaan Dengan Analisa “What If” - Pratiwi Setyaning Putri; Hastanto S. M Hastanto S. M (FORUM MEKANIKA, 2019)
This study aims to analyze corrective actions that can be done if there is a project delay in one of the activities. Data collection techniques are carried out by observation. The gap between the actual and planned scheduling level (productivity gap) is a problem that must be evaluated and the root cause that causes the decline in work productivity is sought. After further evaluation, it is planned to re-target the acceleration that will be achieved both in the short and long term. The acceleration method for scheduling the duration of the project is done by the critical path method or CPM (Critical Path Method) for further development of corrective actions that can be done to overcome the delay in the duration of the project.